Evaluation of antibiotic resistance, toxin-antitoxin systems, virulence factors, biofilm-forming strength and genetic linkage of Escherichia coli strains isolated from bloodstream infections of leukemia patients - Mahdaneh Roshani; Mohammad Taheri; Alireza Goodarzi; Rassoul Yosefimashouf; Leili Shokoohizadeh (BMC Microbiology, 2023)
Abstract Background One of the most common complications in patients with febrile neutropenia, lymphoma, leukemia, and multiple myeloma is a bloodstream infection (BSI). Objective This study aimed to evaluate the antibiotic resistance patterns, virulence factors, biofilm-forming strength, and genetic linkage of Escherichia coli strains isolated from bloodstream infections (BSIs) of leukemia patients. Methods The study conducted in Iran from June 2021 to December 2022, isolated 67 E. coli strains from leukemia patients’ bloodstream infections in hospitals in two different areas. Several techniques including disk diffusion and broth microdilution were used to identify patterns of antibiotic resistance, microtiter plate assay to measure biofilm formation, and PCR to evaluate the prevalence of different genes such as virulence factors, toxin-antitoxin systems, resistance to β-lactams and fluoroquinolone antibiotics of E. coli strains. Additionally, the genetic linkage of the isolates was analyzed using the Enterobacterial Repeat Intergenic Consensus Polymerase Chain Reaction (ERIC-PCR) method. Results The results showed that higher frequency of BSI caused by E. coli in man than female patients, and patients with acute leukemia had a higher frequency of BSI. Ampicillin and Amoxicillin-clavulanic acid showed the highest resistance, while Imipenem was identified as a suitable antibiotic for treating BSIs by E. coli. Multidrug-resistant (MDR) phenotypes were present in 22% of the isolates, while 53% of the isolates were ESBL-producing with the blaCTX-M gene as the most frequent β-lactamase gene. The fluoroquinolone resistance genes qnrB and qnrS were present in 50% and 28% of the isolates, respectively. More than 80% of the isolates showed the ability to form biofilms. The traT gene was more frequent than other virulence genes. The toxin-antitoxin system genes (mazF, ccdAB, and relB) showed a comparable frequency. The genetic diversity was detected in E. coli isolates. Conclusion Our results demonstrate that highly diverse, resistant and pathogenic E. coli clones are circulating among leukemia patients in Iranian hospitals. More attention should be paid to the treatment and management of E. coli bloodstream infections in patients with leukemia.